Re-Evaluating Microfinance : Evidence from Propensity Score Matching - Cintina, Inna (World Bank, Washington, DC, 2017)
This paper evaluates effectiveness of microfinance using Propensity Score Matching (PSM) method applied to data collected in a recent randomized control trial. This method allows one to answer an additional set of questions not answered by the original study and provide more nuanced evidence by comparing Microfinance Institution (MFI) borrowers to those without any loans and those with prior loans from other sources. It is argued that this unique setting with two comparison groups allows us to shed light on the unobservable entrepreneurial spirit bias and provides upper and lower bounds on the true microfinance impact. The results suggest that microfinance can make a modest difference for some households in several expenditure categories.